Impact of the DSM-V Attention Deficit Hyperactivity Disorder Criteria for Diagnosing Children With High IQ. - Thongseiratch, Therdpong; Worachotekamjorn, Juthamas (Psychological Reports, 2016)
This study compared the number of attention deficit hyperactivity disorder (ADHD) cases defined by Diagnostic and Statistical Manual (DSM)-IV versus DSM-V criterion in children who have learning or behavioral problems with high IQ. The medical records of children ⩽15 years of age who presented with learning or behavioral problems and underwent a Wechsler Intelligence Scale for Children (WISC)-III IQ test at the Pediatric Outpatient Clinic unit between 2010 and 2015 were reviewed. Information on DSM-IV and DSM-V criteria for ADHD were derived from computerbased medical records. Twenty-eight children who had learning or behavioral problems were identified to have a full-scale IQ ⩾ 120. Sixteen of these high-IQ children met the DSM-IV criteria diagnosis for ADHD. Applying the extension of the age-ofonset criterion from 7 to 12 years in DSM-V led to an increase of three cases, all of which were the inattentive type ADHD. Including the pervasive developmental disorder criterion led to an increase of one case. The total number of ADHD cases also increased from 16 to 20 in this group. The data supported the hypothesis that applying the extension of the age-of-onset ADHD criterion and enabling the diagnosis of children with pervasive developmental disorders will increase the number of ADHD diagnoses among children with high IQ.